Peran Tutorial PAI UPI dalam Penguatan Nilai Religius dan Karakter Mahasiswa Administrasi Pendidikan : The Role of PAI Tutorial at Universitas Pendidikan Indonesia in Strengthening the Religious Values and Character of Educational Administration Students - April Maulidia Sukma; Istighfari Puspa Qirana; Nur Azizah; Triana Erna Amelia; Edi Suresman (DIRASAH: Jurnal Kajian Islam, 2026)
This study aims to analyze the impact of campus religious activities, including Islamic Education Tutorial (PAI Tutorial), BBQ (Qur’an Reading Guidance), and BTQ (Qur’an Reading and Writing Program), on Islamic understanding and character development among students of the Educational Administration Study Program at Universitas Pendidikan Indonesia. The PAI Tutorial program is implemented through a participatory mentoring system conducted by senior students, involving lectures, thematic discussions, reflective learning, and material documentation. Meanwhile, BBQ and BTQ activities focus on improving students’ ability to read the Qur’an, correcting tajwid, and strengthening Qur’anic literacy. This research employed a qualitative approach with a descriptive method to explore the implementation process and students’ experiences in internalizing Islamic values. Data were collected through observation and in-depth interviews with participating students and analyzed descriptively based on cognitive, affective, and psychomotor aspects. The findings reveal that these religious activities contribute significantly to enhancing students’ Islamic understanding, improving Qur’an reading skills, and fostering religious character, particularly in ethics, responsibility, discipline, and spiritual awareness. This study is expected to provide evaluation material and recommendations for universities in optimizing religious development programs as part of holistic student character and spiritual development.